Apolipoprotein E Gene Variants and Risk of Coronary Heart Disease: A Meta-Analysis. (27th October 2016) - Xu, Min; Zhao, Jun; Zhang, Yu; Ma, Xu; Dai, Qiaoyun; Zhi, Hong; Wang, Bei; Wang, Lina
Abstract : Objectives . Apo E genes involved in lipoprotein synthesis and metabolism are considered one of the candidates to CHD. However, the results remain conflicting. Methods . We performed this meta-analysis based on 30 published studies including 11, 804 CHD patients and 17, 713 controls. Results . Compared with the wild genotype E3/3, the variant genotypes ApoE E3/4 and E4/4 were associated with 22% and 45% increased risk of CHD, respectively (E3/4 versus E3/3: OR = 1.22, 95% CI = 1.15–1.29; E4/4 versus E3/3: OR = 1.45, 95% CI = 1.23–1.71). Besides, compared with ε 3 allele, carriers with the ε 4 allele had a 46% increased risk of CHD (OR = 1.46, 95% CI = 1.28–1.66), while the ε 2 had no significantly decreased risk of CHD. In the subgroup analysis by ethnicity, ε 4 had a 25% increased risk of CHD in Caucasians (OR = 1.25, 95% CI = 1.11–1.41), and the effects were more evident in Mongolians (OR = 2.29, 95% CI = 1.89–2.77). The ε 2 allele had a decreased risk of CHD in Caucasians (OR = 0.84, 95% CI = 0.74–0.96), but not in Mongolians. Conclusions . The analysis suggested that ApoEε 4 mutation was associated with the increased risk of CHD, while ApoEε 2 allele had a decreased risk of CHD just in Caucasians.